PENGARUH SENAM TERA TERHADAP KADAR GULA DARAH LANSIA DENGAN DIABETES MELITUS DI KECAMATAN SUMBERSARI KABUPATEN JEMBER - Firdha Novitasari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2013)
Diabetes mellitus is kind of diseases often suffered by elderly people and it marked by increase of glucose rate in blood. Many kind of therapy have been done to cure their hiperglikemia both farmacology and non farmacology. One of non farmacology therapy that can be their alternative is tera exercise. Tera exercise can decrease hiperglikemia by increasing glucose uptake in skeletal muscle and repairing of insulin sensitivity. This research aimed to find out the influence of tera exercise to blood glucose level. This research used Pra experiment desigh by one group pre-test and post-test design. The number of sample was 35 elderly people whom suffering diabetes mellitus. The blood glucose level of each sample is measured before and after tera exercise, then the different of them is analized to identify the influence of tera exercise. By using sample paired t-test, the result of this research is t count value 14,082, t table value 2,032. Regarding that t count > t-table so Ho is rejected. It can be conclude that tera exercise have influence to blood glukose level in elderly people with diabetes mellitus in Sumbersari Disctric Jember Recidance.